Discovering the Meaning of Leadership: A Canadian First Nations Exploration - Kwantes, Catherine T.; Stonefish, Twiladawn (Journal of Aboriginal Economic Development)

(untitled) (Captus Press, 2019)
First Nations Canadians are in a unique cultural context, with values resulting from both traditional, heritage influences and Eurocentric Canadian influences. Different patterns of endorsing heritage versus mainstream values have resulted. This research examined leadership preferences in First Nations individuals. Linking acculturation patterns to descriptors of leadership attributes that enhance or inhibit outstanding leadership, characteristics of leadership prototypes were developed for members of four acculturative strategy groups. These leadership prototypes were then compared with existing academic leadership theories.